Réponses

2014-05-05T17:44:01+02:00
Je résous l'équation :

2u + 8 = 40
2u = 40 - 8
2u = 32
u = 32/2
u = 16

2u + 8 - 8 = 40 - 8
2u = 32
u = 32/2
u = 16

2u = 32
u = 32/2
u = 16

2u/2 = 32/2
2u = 32
u = 32/2
u  = 16

u = 16

u = 16
résous l'équation :

2u + 8 = 40
2u = 40 - 8
2u = 32
u = 32/2
u = 16

2u + 8 - 8 = 40 - 8
2u = 32
u = 32/2
u = 16

2u = 32
u = 32/2
u = 16

2u/2 = 32/2
2u = 32
u = 32/2
u = 16

u = 16
u = 16
  • Utilisateur Brainly
2014-05-05T18:28:43+02:00
Bonjour, 

Résoudre les équations :


2u + 8 = 40
2u = 40 - 8
2u = 32
u = 32/2
u = 16 

2u + 8 - 8 = 40 - 8
2u = - 8 + 8 + 40 - 8
2u = 32
u = 32/2
u = 16 

2u = 32 
u = 32/2
u = 16

2u/2 = 32/2 
2u = 32
u = 32/2
u  = 16

u = 16

Si tu as des questions, n'hésite pas! =)